Group photo of the participants of the F2R-CWANA inception workshop for Egypt and Sudan - Baum, Michael; Al-Zu'bi, Maha (International Center for Agricultural Research in the Dry Areas, 2023)
Group photo of the participants of the F2R-CWANA inception workshop for Egypt and Sudan.